دور نظام إدارة الصحة والسلامة المهنية - عاد ،محمد الصغير; علماوي ،أحمد (جامعة الوادي University of Eloued, 2024)
The study dealt with one of the quality systems, which is (OHSMS) on improving the social performance of the National Drilling Company (ENAFOR). By analyzing 45 employee questionnaires, the researchers used Partial Least Squares (PLS) for Structural Equation Modeling to assess the influence of OHSMS dimensions, such as policies, planning, implementation, review, and compliance. The findings revealed a significant positive relationship between OHSMS elements and social performance improvement, except for legal compliance, which had a negative effect due to the company's mobile nature. This provided insights into how each requirement affects the company’s social performance.
The role of the occupational health and safety management system (15045001:2018) in improving the performance of the economic institutionCase study of the National Exploration Corporation ENAFOR - Hassi Messaoud
Keywords: أنظمة الجودة; نظام إدارة الصحة والسلامة المهنية; تحسين أداء المؤسسة; Quality systems; corporate; performance; social performance